Microbial Transmission 2019
DOI: 10.1128/9781555819743.ch18
|View full text |Cite
|
Sign up to set email alerts
|

Transmission in the Origins of Bacterial Diversity, From Ecotypes to Phyla

Abstract: Any two lineages, no matter how distant they are now, began their divergence as one population splitting into two lineages that could coexist indefinitely. The rate of origin of higher-level taxa is therefore the product of the rate of speciation times the probability that two new species coexist long enough to reach a particular level of divergence. Here I have explored these two parameters of disparification in bacteria. Owing to low recombination rates, sexual isolation is not a necessary milestone of bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 198 publications
3
29
0
Order By: Relevance
“…Some species show multiple peaks of divergence for high values of d , consistent with the presence of subspecies [36], ecotypes [53, 54], or other strong forms of population structure. These coarse groupings have been observed previously and are not our primary focus here.…”
Section: Resultsmentioning
confidence: 98%
“…Some species show multiple peaks of divergence for high values of d , consistent with the presence of subspecies [36], ecotypes [53, 54], or other strong forms of population structure. These coarse groupings have been observed previously and are not our primary focus here.…”
Section: Resultsmentioning
confidence: 98%
“…An extensive study on the dynamics of bacterial speciation showed that among individual bacterial species, so-called ecotypes comprising ecologically distinct bacterial populations can occur [35]. In B. cereus s.l., seven thermal ecotypes adapted to different thermal niches were proposed [36], which correlate well with ribosomal protein profiles [37] and the group's phylogeny [22].…”
mentioning
confidence: 99%
“…Perhaps the best example of a highly diverse and widely distributed microbe is Prochlorococcus , a global marine cyanobacterium with phylogenetic clades that are known to partition the ocean based on light, temperature, and iron, often referred to as “ecotypes” (Moore et al ; Bouman et al ; Johnson et al ; Rusch et al ). The term ecotype is traditionally defined as ecologically and phylogenetically distinct bacterial populations that can coexist indefinitely (Cohan ). Prochlorococcus ecotypes include the low light clades (eLL), the high‐light, low‐temperature clade (eHL‐I); the high‐light, high‐temperature clade (eHL‐II); and, most recently, two high‐light but low‐iron clades (eHL‐III, eHL‐IV) (Johnson et al ; Rusch et al ).…”
mentioning
confidence: 99%